THE ROLE OF COMMUNITY INSTITUTIONS IN THE FRAMEWORK OF RESIDIVITY DEVELOPMENT FOR INFORMED CITIZENS IN CILEGON CLASS II A COMMUNITY INSTITUTIONS - Muhammad Nasir (Journal of Social Research, 2024)
The role of social institutions in the context of developing prisoners in prisons, especially Cilegon prisons, needs to be increased so that the Binaa residents, after they have finished serving as prisoners, when they are released, have truly become good human beings in the community. Both from a religious and moral perspective and obeying legal regulations. The aim of this research is to determine the role of Cilegon Prison in the context of developing citizens in Class II Cilegon Correctional Institutions. The research method uses a quantitative descriptive approach with data analysis using descriptive statistics. The instrument used in this research is the researcher, who acts as a "human instrument" to obtain the required data. The researchers used observation guidelines, interview guidelines, and questionnaires aimed at each data source, Head of Cilegon Prison, Residents of Cilegon Province Prison. Banten. From the results of research and discussions, it is clear that in the last 3 years the pattern of training inmates in Cilegon prisons has been successful with a significant reduction in criminal cases, especially general criminal cases, and a reduction in recidivists re-entering Cilegon Provincial prisons. Banten, where the consistent application of criminal law for repeat criminals with increased punishment and the provision of special treatment for recidivist prisoners, is expected to reduce the number of recidivist prisoners. In general, there is no difference in the mechanism for training ordinary prisoners and recidivist prisoners. The form of guidance for recidivist prisoners is more focused on independent activities, so that it is hoped that recidivists who have already committed crimes will no longer commit crimes and after leaving their sentence will be well received by the outside community